Orthogonal Space-Time Block Coding for V2V LOS Links with Ground Reflections - Gaitán, Miguel Gutiérrez (2022)
This work presents a capacity analysis of Space-Time Block Codes (STBC) for Vehicle-to-Vehicle (V2V) communication in Line-of-Sight (LOS). The aim is to assess how this type of coding performs when the V2V LOS channel is influenced by ground reflections. STBCs of various coding rates are evaluated using antenna elements distributed over the surface of two contiguous vehicles. A multi-ray tracing tool is used to model the multiple constructive/destructive interference patterns of the transmitted/received signals by all pairs of Tx-Rx antenna links. Simulation results show that STBCs are capable of counteracting fades produced by the destructive self-interference components across a range of inter-vehicle distances. Notably, the effectiveness in deep fades is shown to outperform schemes with exclusive receive diversity. Higher-order STBCs with rate losses are also evaluated, showing interesting gains even for low coding rate performance, particularly, when accompanied by a multiple antenna receiver. Overall, these results can shed light on how to exploit transmit diversity in slow fading vehicular channels.